Investigation of drift dynamics and injection stability of high-current electron beam with picosecond resolution - Yalandin M. I.; Reutova A. G.; Sharypov K. A.; Shpak V. G.; Shunailov S. A.; Ulmasculov M. R.; Mesyats G. A. Gennady Andreyevich (2009, 2009)
В фонде НТБ ТПУ отсутствует